AB0172 EXPRESSION OF SLAMF6 AND ITS FUNCTIONAL SIGNIFICANCE IN PODOCYTES OF LUPUS NEPHRITIS. (June 2019) - Igawa, Takashi; Ichinose, Kunihiro; Eguchi, Mizuna; Okamoto, Momoko; Endo, Yushiro; Tsuji, Sousuke; Takatani, Ayuko; Shimizu, Toshimasa; Sumiyoshi, Remi; Koga, Tomohiro; Kawashiri, Shin-Ya; Iwamoto, Naoki; et al.
Abstract : Background: Systemic lupus erythematosus (SLE) is multisystem disorder that is caused by tissue damage resulting from antibody and complement-fixing immune complex deposition. Lupus nephritis (LN) is frequent complication and one of the most serious manifestations of SLE. The expression of nephrin, as podocyte marker, is reduced in various renal diseases that develop into nephrotic syndrome 1) . The alteration of the structural protein in podocytes is known as a mechanism of proteinuria in LN. Objectives: The signaling lymphocyte activation molecule family (the SLAM family) of type I transmembrane receptors consists of nine related members of the immunoglobulin superfamily and has been reported to mediate important regulatory signals between immune cells through their homophilic and heterophilic interactions 2) .The 1q23 region ( Sle1b region in mouse) on human chromosome 1 including the SLAMF cluster of genes, containing SLAMF6 has been identified as a lupus susceptibility locus 3) .It has been shown that the expression of signaling lymphocyte activation molecule family 6 (SLAMF6) is enhanced in CD4+T cells of SLE patients and is involved in IL-17 production 4) . We sought to examine the functional role of SLAMF6 in lupus podocytes. Methods: We evaluated the co-expression of nephrin, a podocyte marker and SLAMF6 in kidney of normal controls and LN patients, also in B6 and MRL/ lpr mice at the age of 8wk and 16wk by immunofluorescence analysis. We also examined nephrin positive SLAMF6 expression in isolated podocytes from B6 and MRL /lpr kidneys. Then, we analyzed the expression of SLAMF6 in CD4+T cells of isolated kidney and spleen in B6 and MRL/ lpr mice. We treated human podocytes with IgG from healthy individuals and LN patients for 24 h and 48h and analyzed the expression of SLAMF6 by real-time PCR. Results: In the histopathology, the expression of SLAMF6 was increased in nephrin positive area in LN patients and MRL/ lpr mice compared to each control groups. Although the expression of nephrin in MRL /lpr mice kidney at 16 wk old decreased compared to B6 mice at same age, the expression of SLAMF6 in podocytes increased in diseased MRL /lpr mice compared to B6 mice. Similarly, the expression of SLAMF6 in CD4+ T cells increased in diseased MRL /lpr mice kidney and spleen compared to B6 mice. The level of SLAMF6 mRNA elevated in human podocytes exposed to LN-derived IgG compared to healthy individuals-derived IgG. Conclusion: The expression of SLAMF6 is enhanced in LN podocytes, suggesting that the possibility of cooperating with CD4+T cells contributing to its dysfunction. Further examination is needed to investigate in detail how SLAMF6 is involved in the development of LN in the future. References: [1] J Am Soc Nephrol. 2003Aug;14(8):2063-71., [2] Nat Rev Immunol. 2003Oct;3(10):813-21., [3] Nat Rev Rheumatol. 2010Jun;6(6):348-57., [4] J Immunol2012; 188:1206-1212. Disclosure of Interests: Takashi Igawa: None declared, Kunihiro Ichinose: None declared, Mizuna Eguchi: None declared, Momoko Okamoto: None declared, Yushiro Endo: None declared, Sousuke Tsuji: None declared, Ayuko Takatani: None declared, Toshimasa Shimizu: None declared, Remi Sumiyoshi: None declared, Tomohiro Koga: None declared, Shin-ya Kawashiri: None declared, Naoki Iwamoto: None declared, Mami Tamai: None declared, Hideki Nakamura: None declared, Tomoki Origuchi: None declared, Atsushi Kawakami Grant/research support from: Astellas Pharma, Consultant for: Astellas Pharma, Speakers bureau: Astellas Pharma